Towards hybrid AC/DC microgrids: Critical analysis and classification of protection strategies. (July 2018) - Mirsaeidi, Sohrab; Dong, Xinzhou; Said, Dalila Mat
Abstract: Hybrid AC/DC microgrids are arising as an interesting approach as they combine the prominent features of AC and DC networks and do not require excessive modifications in the distribution network. However, protection of such microgrids suffers from several challenges including limited fault current contribution of inverter-based DG sources in the islanded mode, inability of single-setting overcurrent relays in protection of dual-mode microgrids, selection of a proper grounding system, and lack of natural zero-crossing current. The aim of this paper is to provide a comprehensive review of the available strategies for protection of hybrid AC/DC microgrids. Apart from describing the most relevant options presented to date and classifying them into specific groups, a critical analysis is performed, in which the main challenges of each approach are presented. Finally, some conclusions and recommendations for the protection of future hybrid AC/DC microgrids are pointed out. Highlights: A review on the available strategies for protection of hybrid AC/DC microgrids. A critical analysis is performed to compare the available protection strategies. Some recommendations for protection of future hybrid microgrids.